WORK LIFE BALANCE, BURNOUT, AND JOB CHARACTERISTICS OF WOMEN EMPLOYEES ON JOB SATISFACTION - Qomariah Lahamid; Dwi Kurniawati; Ulfiah Nofita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Job satisfaction is something that all employees who work in an organization want to achieve, so it is necessary to pay attention to the main aspects to achieve job satisfaction. The purpose of this study was to explore work life balance, burnout and job characteristics associated with job satisfaction of female employees at the Center for Food and Drug Administration - Balai Besar Pengawasan Obat dan Makanan (BBPOM) in Pekanbaru City. This study uses a descriptive study with the intention of explaining work life balance, burnout, job characteristics and job satisfaction felt by BBPOM Pekanbaru female employees. Purposive sampling is used to determine the number of samples to be studied. There were 60 female employees of BBPOM in Pekanbaru City who met the characteristics of the sample. Questionnaire data in the form of statements were analyzed descriptively. The results showed that there were still female employees of BBPOM Pekanbaru City who lacked a sense of work life balance and still felt bored at work. The workload at the office piles up plus the burden on household chores that must be completed. As a result of the imbalance of work life and boredom experienced, some employees do not feel satisfied at work. However, in terms of job characteristics, they feel that the work assigned is in accordance with their expertise. This study can be used as input for organizations to achieve job satisfaction for female employees of BBPOM Pekanbaru City by paying attention to work-life balance.